Faktor-Faktor yang mempengaruhi penawaran tenagakerja di Provinsi Riau tahun (2000-2018) - Neng Murialti (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2019)
This research aims to determine the factors that affect labor supply in Riau Province over a period of nineteen years (2000-2018). From the results of the simultaneous study, it is known that wage level, economic growth, number of family dependents, average length of schooling and total population have a significant effect on labor supply in Riau province, while partially the wage level, number of family dependents, average school duration, and population have a significant effect on labor supply in Riau province, while tpak and economic growth have no significant effect on labor supply in Riau province.